Is there a biological basis in the selection of medicinal plants in the human species? An initial approach based on chemosensory perception of taste - Silva, Temóteo Luiz Lima da; Ferreira Junior, Washington Soares; Albuquerque, Ulysses Paulino (Ethnobiology and Conservation, 2020)
The ability to identify tastes associated with plant chemicals may have favored humans in identifying plant chemists with pharmacological activity throughout human evolutionary history. The genetic basis of taste perception influences people's varying sensitivity to perceive chemical stimuli of taste. This biological basis can play an important role in plant selection to compose local medical systems, given the argument in the ethnobiological literature that plant taste can influence their selection as a medicinal resource. Thus, we sought to investigate whether there is a biological basis in the selection of these resources. Our investigation was made through the survey of ethnobiological data on the knowledge of medicinal plants and sensitivity data on the perception of bitter taste in two local communities. We tested whether local experts and active tasters of medicinal plants are more sensitive to the perception of bitter taste than the rest of the population. Additionally, we evaluated whether people who are more sensitive to bitter taste cite more plants with taste and assign more therapeutic targets to them. We did not corroborate any of our assumptions. It is likely that the bitter taste threshold is not as relevant in the selection of medicinal plants as the processes of cultural transmission.